Corporate risk exposure by implementing sustainable business practices - an African case. (2015) - Santos, Maria Dos; Svensson, Göran; Padin, Carmen; Høgevold, Nils M.
The risk exposure implementing sustainable business practices is not discussed frequently in literature. The objective of this article is to describe a managerial perception of risk exposure by implementing sustainable business practices. The current research has contributed to the provision of empirical support from a business setting in relation to risk exposure as an essential component within the context of company's implementing sustainable business practices. A principal contribution is a model how to manage the risk exposure in the implementation of sustainable business practices in the marketplace and society. Furthermore we propose that it should be considered in further research of business sustainability. We encourage further assessments providing additional insights into the relationship between corporate risk exposure and business sustainability in order to assess the validity of current empirical findings in other industries and countries.